A experimentação como metodologia de ensino e aprendizagem no contexto da Feira de Ciências - Silva, Gabriela Costa e (Universidade Federal do Tocantins, 2023)
This article presents a brief history of the emergence of the Science Fair, as well as the connection between theory and practice, which this event provides, emphasizing the detailing and effectiveness of the Science Fair at the Silva Dourado State School, exposing the description of the experiments of 8th grade elementary school students, Youth and Adult Education class - EJA. Theoretical - conceptual analyzes were carried out for the execution of this study, as well as, through action research, that it is a methodology for investigating educational practices in a collective and collaborative manner and with equivalent theoretical foundation. Thus we seek the contributions of the authors: Moraes (1986), Brasill (2006), Mancuso (1993), Pereira (2000), Mezzari (2011), Santos (2012), among others. In order to understand the Science Fair pedagogical practice through an approach only when it is collaborative and descriptive of the actions and discussions about the theme in the daily lives of these actors.